Documentation of Indigenous Uses and Traditional Practices of Medicinal Plants by Jhecha Community of Upper Beas Valley, Kullu District in North West Himalaya- Ethnomedicinal Practices of Jhecha Community - Rathore, Sumati; Shashni, Sarla; Samant, Sher Singh; Tewari, Lalit Mohan (Indian Forester, 2024)
The present study was carried out during 2022 to 2023 to document the ethnobotanical knowledge of Jhecha community living in the upper Beas valley of Kullu district, Himachal Pradesh during. A total of 47 plant species belonging to 46 genera and 37 families were used by the Jhecha community. Various plant parts are used for curing ailments like cough/cold, headache, toothache, asthma/bronchitis, diarrhea/dysentery, digestive disorders, cuts/wounds, hair loss, skin ailments, fever, hair fall, menstruation problems, veterinary problems, etc. Awareness programmes for the Jhecha community on values, indigenous uses and traditional practices of medicinal plants and conservation are suggested.